Anti-arthritic activity of D-carvone against complete Freund’s adjuvant-induced arthritis in rats through modulation of inflammatory cytokines - Chen, Guifang (Korean J Physiol Pharmacol, 2020)
Chronic joint pain due to loss of cartilage function, degradation of subchondral bone, and related conditions are common plights of an arthritis patient. Antioxidant compounds could solve the problems in arthritic condition. The objective of this study was to evaluate the anti-arthritic activity of D-carvone against complete Freund’s adjuvant (CFA)-induced arthritis in rats. D-carvone was orally administered for 25 days at the doses of 30 and 60 mg/kg against CFA-induced arthritic rats. Changes in body weight, paw swelling, organ index, hematological parameters, oxidative stress markers, inflammatory cytokines, and histopathology were recorded. Oral treatment of D-carvone significantly improved the body weight, reduced the paw swelling, edema formation, and organ index in arthritic rats. The levels of white blood cells were reduced, red blood cells and hemoglobin levels were improved in D-carvone treated arthritic rats. Lipid peroxidation levels were lowered whereas enzymatic and non-enzymatic antioxidants were significantly elevated by D-carvone administration against arthritic rats. D-carvone significantly modulated inflammatory cytokine levels and improved the ankle joint pathology against CFA-induced arthritic inflammation. In conclusion, D-carvone proved significant anti-arthritic activity against CFA-induced arthritis in rats.